Value of the Cervical Auscultation in Patients Affected by Neurogenic Dysphagia - Fontoura, Elisiane Godoy (International Archives of Otorhinolaryngology, 2009)
Introduction: The cervical auscultation is an instrumental resource used in the functional clinical phonoaudiological approach of feeding and the pulmonary auscultation is a semiotic method for clinical exploitation of the thorax and the heart. Objective: To relate noises from cervical and pulmonary auscultations. Method: Prospective, clinical and experimental, quantitative and comparative study between the cervical and the pulmonary auscultations and sample composed by 19 adult patients with clinical diagnosis of oropharyngeal neurogenic dysphagia, after encephalic vascular accident, with mean age of 59.11 years. We established percentages for variables considering two evaluators. The statistical analysis confirms the presence of slight dysphagia in 66.67%; moderate dysphagia in 16.67% and severe dysphagia in 16.67%. In the cervical auscultation the presence of dry clicks occurred between 42.11% and 78.95% for the different evaluators, and we observed a higher frequency of alterations for evaluator 1. In the pulmonary auscultation the higher frequency was of normal vesicular respiration for both evaluators. We also verified a significant difference between the levels of dysphagia for the cervical and pulmonary auscultations variables, whose correlation shows a low concordance; and a significant discordance between the evaluators for the cervical auscultation and perfect concordance for the pulmonary auscultation. Conclusion: there is no relationship between the noises listened, even with the respiratory function as a base and with the evaluation region being close; but we confirm a relation between dysphagia and pulmonary auscultation, whose results set a frequency of 100% of alterations in the pulmonary auscultation in the dysphagia pictures, with moderate and severe affection levels.